Financialization and the nonfinancial corporation: an investigation of firmlevel investment behavior in the U.S., 1971-2011 - Leila E. Davis (University of Massachusetts, Department of Economics, 2013)
Changes in the portfolio and financing behavior of nonfinancial corporations (NFCs) over the post- 1970 period point to the financialization of the nonfinancial corporation and raise the question of accompanying changes in fixed investment behavior. Using a firm-level panel, this paper econometrically investigates the relationship between financialization and investment, exploring the implications of changes in financing behavior, increasingly entrenched shareholder value norms, and rising firm-level demand volatility for investment by NFCs in the U.S. between 1971 and 2011. Shareholder value norms and firm-level volatility are, in particular, identified as characteristics of the post-1970 U.S. economy that are associated with a significant decline in NFC investment rates. The analysis also highlights key differences by firm size. In particular, shareholder value norms are found to primarily influence the investment behavior of large NFCs, while rising volatility most substantially impacts small firms.
Keywords: 330